How markets for goods and labor must adapt to allow development - Fafchamps, Marcel (Henry Stewart Talks, 2016)
Labor allocation mechanisms, Labor markets and development, The entrepreneurship revolution, The industrial revolution, Social norms in the labor domains, Domain coexistence